Robert Serumaga and the golden age of Uganda's theatre : solipsism, activism, innovation (1968-1978) - Seremba, George Bwanika (Trinity College (Dublin, Ireland). Department of Drama, 2008)
The theoretical methodology employed in the research and writing of this thesis is primarily postcolonial. Though comparatively nuanced, poststructuralism is also employed. The emphasis in the latter is on the Foucaldian position with regard to history, and also on deconstruction. This is an examination of the work of Ugandan playwright Robert Serumaga, and what I have designated as the ‘Golden Age of Uganda’s Theatre’ (1968-1978). The key issue is the question of individualism, or its extreme form — solipsism, on the one hand; and activism, or a social conscience, on the other. In addition, the thesis also examines the question of theatrical innovation in Serumaga’s plays. There is a comprehensive introduction to Serumaga the man, as well as the historical context against which his plays unfold. The first chapter focuses on the theatrical history, the precursors to Serumaga as well the Golden Age. Serumaga’s work is examined in chronological order starting with his very first play A Play in Chapter 2; The Elephants, in Chapter 3; and Majangwa in Chapter 4. Chapter 5 is devoted to the regimen and methodology of Serumaga’s company the Abafumi and concentrates on the first of Serumaga’s largely semiological, and unscripted drama, Renga Moi (Red Warrior). Amayirikiti (The Flame Tree), the second of the two ‘ritual dramas’, though not the focal point is also discussed in the chapter.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin